การศึกษาการนำไอน้ำที่ความดันต่ำกลับมาใช้ใหม่โดยสตีมอีเจคเตอร์ - ไชยณรงค์ จักรธรานนท์ (จุฬาลงกรณ์มหาวิทยาลัย, 1997)
A steam ejector is designed for converting energy in a form of pressure into kinetic energy in a form of supersonic velocity for entrainment the low pressure steam and mixed them together. By flowing pass through the nozzle that is changed in each cross section area. The objectives of this research are studying to find the parameter that concern with designing steam ejector and able to recovery the low pressure steam and bring it into process again for saving energy. Test will be done by using pressure ration Po1/Po2 at 4 locations of primary nozzle with 4 Mach numbers, these are 1.7, 1.9, 2.2 and 2.4 by compare with variation of entrainment ratio for knowing the available efficiency in each case. If the static pressure at exit nozzle match to secondary pressure, can give the higher efficiency of system that can neglect the effect from shoch wave that maybe happen. And also optimize length of distance from primary nozzle to mixing throat will give the higher efficiency. The pressure that is chosen will relate with Mach No. at exit primary nozzle for matching pressure. By this research hold that the flow is adiabatic flow in all mixing length. Model loss of steam ejector can predict the available efficiency and give idea to develop steam ejector efficiency is higher. Adjustment the value of Ctau is appropriate with any model will can predict the result of loss is more accuracy.